2012
DOI: 10.1111/j.1365-2834.2012.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

The systems approach to error reduction: factors influencing inoculation injury reporting in the operating theatre

Abstract: A significant number of inoculation injuries are not reported. Factors influencing under-reporting were identified. This knowledge can assist managers in improving reporting and encouraging a robust safety culture within operating departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…It is, in line with high-reliability theory [ 14 ], necessary to raise this issue further to understand how subculture can facilitate reporting so that appropriate action can be taken to prevent or reduce the risk of incidents and injuries. Healthcare researchers [ 12 ] and other high reliability organizations [ 13 ] have similarly put forth issues of subculture and workplace climate factors, such as burdensome administration and lack of feedback, as obstacles for reporting. Barach and Small [ 30 ] have, in other types of aviation, noted similar results where fear of reprisal, lack of trust, code of silence, and skepticism are mentioned as reporting barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, in line with high-reliability theory [ 14 ], necessary to raise this issue further to understand how subculture can facilitate reporting so that appropriate action can be taken to prevent or reduce the risk of incidents and injuries. Healthcare researchers [ 12 ] and other high reliability organizations [ 13 ] have similarly put forth issues of subculture and workplace climate factors, such as burdensome administration and lack of feedback, as obstacles for reporting. Barach and Small [ 30 ] have, in other types of aviation, noted similar results where fear of reprisal, lack of trust, code of silence, and skepticism are mentioned as reporting barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 55% of surgeons and 91.5% of theatre nurses report all or more than 50% of mucocutaneous and percutaneous injuries occurring in operating theatres. The cumbersome administrative procedure, the attitude, personal characteristics of the surgeon, and lack of feedback were given as important reasons for not reporting incidents [ 12 ]. According to Roberts and Rousseau [ 13 ], can management attitudes and institutional climate greatly influence the success or failure of reporting efforts in high reliability organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Although prompt reporting of sharps injuries is a required (and encouraged) part of most health care organizations’ policies and procedures, perioperative personnel often underreport their injuries . In a survey of 315 surgeons and perioperative nurses, 58% responded that they reported one or more injuries within the past five years; however, only 55% responded that they reported every injury to their organization . In another survey of 164 surgeons at three general hospitals, the researchers assessed the number of sharps injuries and the number of injuries reported and found that 120 (73.2%) of the respondents had experienced an injury in the past year.…”
Section: Sharps Injury Reportingmentioning
confidence: 99%
“…Underreporting of workplace injuries in the U.S. is well documented [ Azaroff, et al 2002 , Boden and Ozonoff 2008 , Rosenman, et al 2006 ]. This is seen among health care workers in particular [ Galizzi, et al 2010 ] and specifically for musculoskeletal [ Menzel 2008 , Siddharthan, et al 2006 ] and sharps injuries [ Alvarado-Ramy, et al 2003 , Cutter and Jordan 2013 , Doebbeling, et al 2003 , Elder and Paterson 2006 , Osborne 2003 , Panlilio, et al 2004 , Tandberg, et al 1991 , Voide, et al 2012 ]. The published rates for underreporting sharps injuries vary substantially and are not based on directly comparing survey data with administrative data containing the same group of subjects.…”
Section: Introductionmentioning
confidence: 99%